Genetic diversity of Japanese quail cathelicidins - Ishige, Taichiro (Poult Sci, 2021)
Japanese quail is a low-fat, meat-bird species exhibiting high disease resistance. Cathelicidins (CATHs) are host defense peptides conserved across numerous vertebrate species that play an important role in innate immunity. The activity of host defense peptides can be affected by amino acid substitutions. However, no polymorphisms in avian CATH genes have been reported to date. The aim of this study was to clarify the polymorphisms in CATHs in Japanese quail. DNA for genomic analyses was extracted from the peripheral blood of 99 randomly selected quail from 6 inbred lines. A total of 6, 4, 6, and 4 CjCATH1, -2, -3, and -B1 alleles were identified, respectively. Nine haplotypes, including 4 strain-specific haplotypes, were identified by combining alleles at the CjCATH1, -2, -3, and -B1 loci. In addition, 2 and 1 amino acid substitutions (I145F, Q148H, and P245H) predicted by PROVEAN and PolyPhen-2 to have deleterious effects were detected in CjCATH2 and -B1, respectively. Synthetic CjCATH2 and -B1 peptides exhibited greater antibacterial activity against Escherichia coli than chicken CATH2 and -B1, respectively. Furthermore, the CjCATHB1∗04 peptide exhibited less potent antimicrobial activity than other CjCATHB1 peptides examined. This is the first report of amino acid substitutions accompanied by changes in antibacterial activity in avian CATHs. These findings could be employed as indicators of improvements in innate immune response in poultry.